Analisis Faktor-faktor yang Mempengaruhi Tingkat Pendapatan Masyarakat Desa Dahana Alasa Kabupaten Nias Utara Tahun 2025 - Lahagu, Winner Purnama Sari; Laoli, Bezisokhi; Telaumbanua, Wahyutra Adilman; Laoli, Eka Septianti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The research was motivated by the persistent issue of low income among rural residents, despite various government support programs. This study was conducted to analyze the influence of capital, work experience, and government policy on the income levels of the community in Dahana Alasa Village, North Nias, in 2025. A quantitative research method was employed, using a descriptive analytical approach. The population of the study consisted of 117 residents, from which a simple random sample of 15 respondents was selected. Data were collected through structured questionnaires with closed-ended questions. The findings show that the majority of respondents are farmers (66.67%), women (60%), aged between 45–60 years (80%), and have a basic level of education (elementary and junior high school). Capital emerged as the primary obstacle to increasing income. Respondents reported difficulties in obtaining business capital and accessing credit facilities, while existing government capital assistance programs were perceived as uneven and ineffective. Although work experience contributed to decision-making and skill development, its impact on income remained limited without sufficient capital support, particularly among farmers. Moreover, government policies were found to be less effective due to inadequate program dissemination and poor access to information. The study concludes that low income is primarily due to limited capital, ineffective use of work experience, and suboptimal government policy implementation. Recommendations include improving capital access, providing skills training, and enhancing communication of government programs.